Kepatuhan Negara-Negara ASEAN untuk Tidak Campur Tangan dalam Menangani Persekusi Etnis Rohingya di Myanmar - Indra, Erizon; Utomo, Tri Cahyo (Journal of International Relations, 2018)
Rohingya ethnic persecution case became the focus of the international community,especially ASEAN. The persecution suffered by the Rohingyas included murder, rape andarson. This makes the ASEAN countries are expected to take concrete action in resolvingthis conflict. In carrying out the organizational functions, ASEAN countries collide withthe principle of non-intervention adopted by ASEAN. This study aims to determine theprofile and capacity of ASEAN in addressing the conflicts that occurred in Myanmar. Thisresearch uses compliance theory and international organization in understanding theattitude of ASEAN countries in following up the Rohingya ethnic persecution case. Indealing with the Rohingya crisis, ASEAN was unable to apply strict sanctions as it relatesto the principle of non-intervention which turned out to be a form of resistance for ASEANto be able to resolve the political and security issues strictly. This is what makes theproblem vulnerable to recurrence. The result of this research shows that ASEAN putforward the peaceful road map and third party mediation in resolving conflict. Inaddressing the Rohingya crisis, ASEAN uses other measures and efforts of humanitariandiplomacy.